Pengalaman Spiritualitas dan Psikologis Mahasiswa melalui Praktik Membaca Al-Qur’an Harian: Studi Fenomenologis - Nur Isra’ Ahmad; Farhah Utami; Kartini; Ushwa Dwi Masrurah Arifin Bando (Jurnal Pendidikan Agama Islam, 2026)
Students in the digital era are vulnerable to psychological crises due to academic pressure and technological distractions, so they need coping strategies to maintain mental balance and strengthen religious character. This study aims to describe the spiritual and psychological experiences of students through the practice of reading the Qur'an daily, using a phenomenological qualitative approach to 15 informants from one of the campuses in Makassar who consistently read the Qur'an every day. The results of the study show that reading the Qur'an every day has been proven to have a significant impact on students, both in spiritual and psychological aspects. Spiritually, they feel closeness to Allah SWT, the growth of gratitude, patience, optimism, and the encouragement to istiqamah in worship. Meanwhile, psychologically, students gain inner peace, clarity of mind, the ability to control emotions, and reduced anxiety and stress. This confirms that the practice of reading the Qur'an does not only function as a religious activity, but also as an effective means of reflection in the face of academic and social pressures. The implication of this study is that daily reading of the Qur'an can be used as part of the character development of students in higher education to maintain mental balance while strengthening religiosity.